Clinical Outcomes Associated With Integrated Orthodontic Management of Tipped Teeth: A Retrospective Cohort Analysis of Functional Recovery, Occlusal Stability, Complications, and Retreatment - Lei He; Rujuan Gong (Orthodontics & Craniofacial Research, 2026)
ABSTRACT Background Tipped teeth are frequently managed by orthodontic uprighting, retention, and subsequent tooth‐preserving or restorative care, but real‐world pathways are heterogeneous. Evidence comparing coordinated treatment pathways with less standardised management remains limited, and observational comparisons require careful interpretation. Methods We retrospectively analysed 204 adult patients with at least one tipped tooth requiring clinical management at a single tertiary dental centre from January 2021 to January 2025. The integrated pathway group received orthodontic uprighting followed by standardised retention and coordinated preservation or restorative care ( n = 127). The non‐standard management group included patients treated by direct restorative treatment without orthodontic uprighting ( n = 45) and patients treated orthodontically without standardised retention or coordinated restorative follow‐up ( n = 32). Patients were classified according to the treatment pathway selected at the initial treatment decision and index intervention stage. Outcomes were assessed at the patient level and included satisfactory functional recovery, occlusal stability, complications, retreatment, and an exploratory composite of overall treatment success. Baseline balance was summarised using standardised mean differences in addition to p values. Multivariable logistic regression was used only as an exploratory adjustment for prespecified pretreatment covariates; causal language was avoided. Results Of 242 potentially eligible patients, 38 were excluded, leaving 204 patients for analysis. Satisfactory functional recovery was recorded more often in the integrated pathway group than in the non‐standard management group (89.8% [114/127] vs. 75.3% [58/77], p = 0.006). Occlusal stability was also more frequent (86.6% [110/127] vs. 70.1% [54/77], p = 0.004). Complications occurred in 13.4% (17/127) and 27.3% (21/77), respectively ( p = 0.011), and retreatment was required in 8.7% (11/127) and 18.2% (14/77), respectively ( p = 0.028). Exploratory adjusted estimates suggested higher odds of the composite adverse outcome with severe initial inclination and direct restoration without uprighting; however, the low events‐per‐variable ratio limited model stability and precluded confirmatory interpretation. Conclusion In this retrospective cohort, integrated orthodontic‐retention‐restorative management was associated with more favourable functional and clinical outcomes than heterogeneous non‐standard management. Because treatment selection was not randomised and some outcome definitions relied on routine clinical records, the findings should be interpreted as hypothesis‐generating rather than causal.